Factores asociados a la automedicación en el centro poblado de Llícua, Huánuco - Montero Berrospi, José Manuel (2018)
Introduction: The objective of the present study was to determine if the level of education, monthly income and self-rated severity of discomfort are factors associated with self-medication in the inhabitants of the town center Llícua from June to August 2014. Methods: Survey kind of observational, analytical and cross-quantitative nature. Results: 320 people self-medicating with respect to educational level 11 (84.6%) are illiterate, primary 43 (75.4%), secondary 133 (83.1%), technical / top 129 (78.2%), post-grade 4 (80%) (p = 0.693) compared to monthly income 209 (81.6%) corresponded to an income below average, which was S / 902, and 11 (77.1%) were above average (p = 0.274), finally regarding self-rated severity of discomfort 253 (84.3%) said their discomfort was mild-moderate and 67 (67%) was severe (p = 0). Conclusions: 80% of the study population makes use of self-medication. No association between monthly income and self-medication was found. The perception of severity of the discomfort of mild to moderate hallo associated with self-medication with a value of p = 0.000 and OR = 2.651 and also association between the availability of time and self-medication.